First record of genus Atherimorpha (Diptera: Rhagionidae) in Brazil, with description of a new species - Santos, Charles Morphy Dias Dos (Zootaxa, 2005)
Four of the 22 genera of Rhagionidae have been reported from the Neotropical region, of which only Chrysopilus Macquart has been found in Brazil. The first occurrence of the genus Atherimorpha White is reported from Brazilian territory, and Atherimorpha lamasi sp. n. is described and illustrated.Key words: Atherimorpha, Rhagionidae, Diptera, Neotropics, Taxonomy